Integration in Practice. How do they do it? - Scott, Ann (European Journal for Qualitative Research in Psychotherapy, 2007)
This study examines the phenomenological experience of Christian psychotherapists working with clients in an Integrative Psychotherapy paradigm. A qualitative phenomenological methodology was used in order to give congruency with the subject matter. Eight co-researchers were interviewed and the data obtained was analysed by the Colaizzi method (1978) to ensure the maximum amount of rigour possible. An overall composite description of the phenomenon under investigation was obtained and discussed in light of the existing literature. Common themes emerged showing that faith can be both a help and a hindrance in the therapy room. Whichever is the case, it seems that if the therapist has a faith it cannot be ignored if he/she is to provide a high level of authenticity in relationship with clients. The issue of judgmentalism was figural for many of the co-researchers, revealing the possible dilemma of a conflict between the major person- centred principles of authenticity and deep empathy within the therapeutic relationship. There were some indicators that this may be more of a problem for Christian rather than non-Christian therapists. A number of suggestions for future research were made.